Strategies for Clean Production in Methyl Isocyanate Synthesis for Pesticide Raw Materials - Faisal, Deni; Sulaiman, Fatah; Pramudita, Marta (Universitas Negeri Semarang, 2023)
The increasing demand for pesticides in agriculture has led to a rise in the production of methyl isocyanate, a key intermediate in carbamate pesticide manufacturing. However, this process generates sodium sulfate as a by-product, dissolved in an aromatic solvent, which, if not adequately managed, contributes to environmental pollution and resource inefficiency. Chemical and environmental engineering are crucial in addressing this issue by developing effective separation and recovery methods. One potential solution is the distillation process, which separates sodium sulfate based on boiling point differences with water. However, the effectiveness of this method depends on operational conditions, particularly pressure and sulfuric acid concentration. This research focuses on optimising the recovery of sodium sulfate from methyl isocyanate production waste by investigating different operating pressures (atmospheric, vacuum, and combined) and sulfuric acid concentrations (0 M, 0.07 M, 0.15 M, 0.22 M, and 0.30 M). A recovery efficiency of sodium sulfate as high as 92.5% using vacuum distillation at a 0.22 M sulfuric acid concentration. Additionally, the condensate water contained 98.7% purity, making it suitable as a precursor for struvite fertiliser. Sodium sulfate is used as a raw material in producing insecticidal pesticides, with a purity level of 97.3%. This study demonstrates that an optimised distillation process can enhance the efficiency of pesticide production by minimising waste and maximising resource utilisation, contributing to cost efficiency and environmental in industrial pesticides.